THE EFFECT OF RETURN ON ASSETS (ROA) AND LOAN TO DEPOSIT RATIO (LDR) ON SHARE PRICE IN STATE-OWNED BANKING SUBSECTOR LISTED ON INDONESIA STOCK EXCHANGE: PENGARUH RETURN ON ASSET (ROA) DAN LOAN TO DEPOSIT RATIO (LDR) TERHADAP HARGA SAHAM PADA SUBSEKTOR PERBANKAN BUMN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Ade Fauji; Puji Karniawati (Indonesian Journal of Economy, Business, Entrepreneurship and Finance, 2021)
The stock price circulating in the stock market illustrates the performance of a company. The high low value of the stock price is influenced by various factors, including the company's financial performance. The research aims to test the influence of Return on Asset (ROA) and Loan To Deposit Ratio (LDR) variables on the stock price of the BUMN banking subsectors listed in the Indonesia Stock Exchange period 2011-2019. The methods used in this study are quantitative descriptive methods with correlational analysis, using secondary data with a population of 4 banks. The sampling method used in this study is a method of saturated samples. All population members are used as samples. From the hypothesis test results (Test t), the Return On Asset (X1) is obtained; the calculated t value is greater than the t table (-2,194 > 2,034) with the value sig. 0,035 < sig.0,05 This indicates that Ha1 is accepted, meaning that ROA affects negative and significant to the stock price. While the Loan To Deposit Ratio (X2) variable the count t value is greater than t table (-3,267 > 2,034) with a value sig 0,003 < sig.0,05 This indicates that the Ha2 is accepted, meaning that LDR affects negative and significant to the stock price. Moreover, we obtained the count F value > F table, which is 5,393 > 3,28 and a significant value of 0,009 < sig, 0,05, which means ROA and LDR are simultaneously influential and significant to the stock price. The conclusion from the results of research ROA has a negative and significant effect on the stock price. LDR has a negative and significant effect on the stock price. At the same time, ROA and LDR are simultaneously influential on the stock price.